Ethical leadership and organizational commitment in the Colombian electricity sector: the importance of work self-efficacy - Santiago-Torner, Carlos (2025)
This study analyzes the effect of ethical leadership on organizational commitment, considering work self-efficacy as a mediating variable. Structural equation modeling is used to analyze the proposed relationships. The sample consists of 448 professionals inthe Colombian electricity sector. Ethical leaders increase organizational commitment, specifically the affective, normative, and perceived investment dimensions (Continuance 2), but not the perspective of lack of job opportunities (Continuance 1). Work self-efficacy explains how ethical leadership influences the analyzed dimensions of organizational commitment, with the exception of the lack of job opportunities (Continuance 1). Ethical leadership seeks to meet the socio-emotional needs of followers. When employees feel listened to and valued by the leader, they voluntarily choose to increase their commitment. However, when employees feel trapped in an organization and experience a constant sense of obligation, their discouragement intensifies, and they withdraw emotionally until they are disconnected from the positive effects of ethical leadership and work self-efficacy.